THE CORRELATION BETWEEN STUDENTS INTERESTED IN WATCHING HARRY POTTER AND THE PHILOSOPHERS STONE BY J.K ROWLING MOVIES AND THEIR LISTENING COMPREHENSION - Anisa Septia Megawati (PT. Jurnal Center Indonesia Publisher, 2024)
The principal purpose of this study was to find out; (1) Is there students interested in watching Harry Potter and philosopher’s stone by J.K rowling movie (X) in their listening comprehension (Y), (2) Is there any correlation between students‘ interested in watching Harry Potter and the philosopher’s stone by J.K Rowling movie (X) to listening comprehension (Y). It was carried out to the class XI Science students of SMA Mutiara Palabuhanratu. In this research, a quantitative method is used with the Pearson product moment correlation study to answer the research problem. The population of this research is the students of SMA Mutiara Palabuhanratu class XI IPA for the academic year 2021/2022, totaling 30 students. The sample used is the total population. Tests and questionnaires were used to collect data. After getting the data, the researcher corrected and analyzed the test results. Data analysis using Pearson Product Moment Correlation. The results of the study indicate that the level of significance between the variables X and Y based on the results of the correlation value above rcount = 0.481 rtable (5%) (df = n-2 = 30-2 = 28) rtable = 0.374. So it is clearly stated that rcount is higher than rtable or 0.05 <0.374. The result of the correlation coefficient between the two variables is 0.481. That result indicated that there was a medium correlation between students’ interested s in watching Harry Potter movie and their listening comprehension. This statement was proved based on the result rxy was higher than the rtable (0,481 ≥ 0,374 in significant level 5%) it showed that the null hypothesis (Ho) “There is no relationship between students’ interested in watching Harry Potter movie and their listening comprehension” is rejected and the alternative hypothesis (H1), “There is a positive relationship between students’ interested in watching Harry Potter movie and their listening comprehension” is accepted.